Prevalence and epidemiologic transition of sexually transmitted infections in a Brazilian dermatologic clinic (2012-2019) - Oliveira, Vítor Cercal de; Minato, Arthur Cesar dos Santos; Morita, Mariana Mathias; Oliveira, Júlia Ferreira de; Ishimoto, Letícia Yumi; Cruz, Bianca Latance da; Nakata, Maria Vitória Yuka Messias; Moreira, Lais Gonçalves; Miot, Hélio Amante (Brazilian Journal of Sexually Transmitted Diseases, 2022)
LETTERS TO THE EDITOR